Sustainable management of different systems for recycling end-of-life tyres in China. Issue 7 (July 2021) - Huang, Weilun
Based on a literature review and interviews with experts, the purpose of this article is to investigate the sustainable management of different systems for recycling end-of-life tyres (ELTs) in China. Systems for bicycles (including electric bicycles), electric motorbikes and cars are considered. The article finds there are differences in the price, handling costs, process costs and transport costs. Consequently, most of the recycled ELTs are from cars. Accordingly, an economic model is built to show the difference between the different systems. The results show that the recycling system for ELTs from cars works effectively, whereas that for bicycles and electric motorbikes does not work in China. In addition, a social welfare model is built to discuss the sustainable management of the different systems for recycling ELTs. Based on the results of the model, it is suggested that subsidies could be provided according to the weight of ELTs, and that if subsidies were to be granted specifically for recycling ELTs from bicycles and electric motorbikes this would promote the efficiency and the sustainable management of these recycling systems in China.